Strategi Efektif Simplifikasi Nahwu dalam Percakapan Arab pada Kelas Intensif Daurah Ramadhan - Nur Hanifansyah; Menik Mahmudah (KURAS Institute, 2025)
This study aims to explore effective strategies for simplifying Arabic grammar (nahwu) to enhance maharah kalam (speaking skills) among students participating in the intensive Daurah Ramadhan program at Pondok Pesantren Darullughah Wadda’wah (Dalwa). Using a descriptive qualitative approach, this research involved 60 takhassus students from diverse pesantren backgrounds who had prior knowledge of nahwu and sharaf but still struggled with active Arabic conversation. Data were collected through participatory observation, in-depth interviews with both teachers and students, and documentation of teaching materials and student evaluations. The data analysis employed thematic analysis, involving data reduction, categorization of themes, and interpretation of findings. To ensure data validity, triangulation methods were used, including triangulation of sources (comparing data from interviews and observations) and triangulation of methods (combining observation, interviews, and documentation). The findings reveal that simplified grammar instruction—such as recognizing the implicit meaning of